On the Modernist Frontier: Foreign Art Exhibitions in Russia in the 1890s - Doronchenkov, Ilia A. (Actual Problems of Theory and History of Art, 2020)
The article reconstructs the history of organizing and holding of foreign art exhibitions that took place in Russia in the 1890s. During this period, St. Petersburg and Moscow were the leading locations of the Russian Empire, in which acquaintance, comprehension, and development of Western art practices took place.The article sequentially analyzes the large-scale exhibitions, which allowed the Russian audience, without going abroad, to get a fairly wide idea of the art of France, Holland, England, Belgium, and the countries of Scandinavia in a short period of time. A significant role in this process was played by the curatorial activity of Sergei Diaghilev, whose main goal, according to the author, was to form a new exhibition model in Russia — secession, i.e. a multinational exhibition that gives a pluralistic picture of the quest for contemporary art and focuses on masters with an international reputation. The article analyzes in detail the reasons why the new role of the curator postulated by Diaghilev, as well as the exposition and exhibition format proposed by him, were not fixed on Russian soil.
Keywords: art exhibition; Sergey Dyagilev; art of the end of the 19th century; the origins of modernism